Réponses

2014-03-01T15:14:06+01:00
Bonjour,
                                                                                                   
a) AM = AN= x donc DM = NB = 6 - x d'ou A( MDC ) = A ( NBC ) =  MD fois DC sur 2 = ( 6 - x ) fois 6 sur 2 = ( 6 - x ) fois 3 = 6 fois 3 - x fois 3 = 18 - 3x 

b) A ( AMCN ) = A ( ABCD ) - A ( MDC ) - A ( NBC ) - A ( ABCD ) - 2 fois A ( MDC )
                        A ( AMCN ) = 6² - 2 fois ( 18 - 3x ) = 36 - 36 + 6x = 6x

c) si x = 2cm , A ( MDC ) = A ( NBC ) = 18 - 3 fois 2 = 18 - 6 = 12 cm² et A ( AMCN ) =6 fois 2 = 12 cm²                       
 
 Heureux de t'avoir aider et bonne journée.